1999
DOI: 10.1016/s0370-2693(99)00454-2
|View full text |Cite
|
Sign up to set email alerts
|

On the beta function in supersymmetric gauge theories

Abstract: We re-examine perturbative and nonperturbative aspects of the beta function in N = 1 and N = 2 supersymmetric gauge theories, make comments on the recent literature on the subject and discuss the exactness of several known results such as the NSVZ beta function. (C) 1999 Published by Elsevier Science B.V. All rights reserved

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…The relation with normalization of the gauge coupling and the exact expression of the beta function was found in [27]. A simple exposition is given for example in [28]. is generated, where the determinant is taken to SU (2) and U Sp(N 2 ) as one flavor index.…”
Section: Deformed Conifold As Quantum Moduli Spacementioning
confidence: 99%
“…The relation with normalization of the gauge coupling and the exact expression of the beta function was found in [27]. A simple exposition is given for example in [28]. is generated, where the determinant is taken to SU (2) and U Sp(N 2 ) as one flavor index.…”
Section: Deformed Conifold As Quantum Moduli Spacementioning
confidence: 99%
“…This interpretation is however not valid for finite a for two reasons: firstly the statement that a is proportional to the gauge boson mass is only valid at weak coupling and secondly because (3.6) diverges at strong coupling, g → ∞ where τ → 0, [42,43]. The latter difficulty can be remedied by defining a different scaling function which is still a modular form of weight −2.…”
Section: Duality In Electromagnetismmentioning
confidence: 99%
“…The latter difficulty can be remedied by defining a different scaling function which is still a modular form of weight −2. Seiberg and Witten's expression for τ (u) can be inverted to give u(τ ) [40,41,42,43] …”
Section: Duality In Electromagnetismmentioning
confidence: 99%
“…The massless spectrum of type IIB superstring theory was given in the last section, where we found that in terms of transverse SO (8) 14 The relation between open-and closed-string couplings comes from the vertex operators for open-and closedstrings. The first one acts on the boundary, and the second on the interior of the worldsheet.…”
Section: Type Iib Supergravitymentioning
confidence: 81%
“…The bare lagrangian of an N = 1 supersymmetric gauge theory with generic matter content is given by [13][14][15],…”
Section: The Non-abelian Casementioning
confidence: 99%